Women in the revolution [videorecording] - National Commission for Culture and the Arts (Quezon City : Felta Multi Media Center.)
A television program on the role of women during the Philippine Revolution; includes features on Filipino attire during the revolution and our National Anthem.
Keywords: Women in war -- Philippines